analysis and design of academic information systems at SMAS Al-Multazam Mojokerto - dewi, diva rosalina; Nurcahyawati, Vivine; Ningsih, Norma (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
The institution of SMAS Al-Multazam Mojokerto is an educational institution located in Islamic Education Foundation naunagan Al-Multazam housed in Kepuhanyar Highway No. 24 subdistrict of Mojokerto Mojoanyar. SMAS Al-Multazam in improving service quality of academic, SMAS Al-Multazam issued policies do the migration from manual process becomes a process of tersistem with good match from one of Al-Multazam SMAS mission. The issues facing the SMAS Al-Multazam currently include first, the determination of class time takes a long time because it takes seven days to correct the problem with the entry value. Second, in doing scheduling subjects, often happens to crash on a schedule created. Third, the hardcopy form presence form the crash prone, missing data, error and need a recap of additional fees for doubling documents presensi form. Fourthly, the assessment process be longer when the eleventh semester activities will be performed. Based on some of the problems above, Al-Multazam SMAS requires the presence of the analysis and the design of the academic information system that can do the process of determining the class presensi, data storage, scheduling subjects and calculation value as well as making the report. Academic information system design is done using the stages of the SDLC waterfall method. Analysis and design of information systems academic at Al-Multazam SMAS will produce the document specification of Software Requirements (SKPL) and document design and software architecture (DAPL). The document can be used as the basis for the development of academic information systems.Â Â